Anti-Microbial Activity and Spectro-Chemical Investigation of Ink Extracts of Sepiella inermis (Van Hasselt 1835) - Dasal VASANTHARAJA; Vaithilingam RAVITCHANDIRANE; Veerappan ANANDAN (Notulae Scientia Biologicae, 2014)
The crude petroleum ether and methanol ink extracts of Sepiella inermis were tested for their antimicrobial activity against human pathogenic fungi and bacteria by disc diffusion method. Spectral analysis was carried out by UV-VIS spectrophotometer, FT-IR, Raman IR and GC-MS. Of the two solvent extracts, only methanol extract was active and no activity was detected in petroleum ether extract. The human pathogenic fungus Candida albicans and bacterium Proteus vulgaris were found to be highly sensitive, with an inhibition zone of 20 and 19 mm respectively. GC-MS of methanol ink extract revealed sixteen compounds belonging to the derivatives of dihydroxy indole-2-carboxylic acid and dihydroxyindole. These investigations proved that methanol ink extract of Sepiella inermis possess significant antimicrobial property against both fungus and gram –ve bacteria. Since ink of sepia is available abundantly as a waste material, studies focused on isolation and characterization of bioactive substances pave the way for new antimicrobial compounds.